Mesenchymal Stem Cell Therapy for Chronic Kidney Disease (Renal Failure and Multiple Episodes of Nephrolithiasis): A Case Report - Wang, Sebo Gene; Wang, Sebo Michelle; Hsu, Ming Chu; Wang, Fu Nan (Recent Updates in Disease and Health Research Vol. 4, 2024)
Chronic kidney disease occurs when the kidneys are damaged and unable to filter blood appropriately. It is difficult to regenerate or recover kidney function once it has been compromised. This can result in nephrolithiasis and renal failure. This study aims to discover MSC therapy’s effectiveness in treating Renal failure and Nephrolithiasis. Mesenchymal stem cells (MSCs) are the prime candidates for regenerative medicine and cell therapy. MSCs can be obtained and isolated from a variety of tissues such as the umbilical cord, the placenta, amniotic fluid, adipose tissue, etc. This case report describes a 58-year-old male with a history of recurrent nephrolithiasis, decreased estimated glomerular filtration rate (eGFR), elevated blood urea nitrogen (BUN), and elevated serum creatinine with a concern for chronic kidney disease (CKD), stage 3 development who was treated with a total of four MSCs treatments of 5.0 × 108 MSCs per infusion over the course of two months. Post-treatment five years later revealed no recurrent nephrolithiasis and normal eGFR, serum BUN, and creatinine levels which suggest that MSCs can be a safe and effective modern treatment for CKD and nephrolithiasis. Early diagnosis and treatment with MSC therapy have the potential to improve renal failure and could be the gold standard to prevent future hemodialysis or kidney transplantation.